Risk and protective factors for alcohol use among school-going adolescents in Montevideo (Uruguay). Issue 1 (6th March 2017) - Fernandez, Maria Eugenia; Daset, Lilian; Vanderplasschen, Wouter; Costa Ball, Cesar Daniel; Van Damme, Lore; Vindevogel, Sofie
Abstract : Purpose: The purpose of this paper is to explore risk and protective factors for alcohol use among school-going adolescents in Montevideo (Uruguay). Design/methodology/approach: A self-report survey was administered to 331 school-going adolescents in Montevideo (Uruguay) ( M age =13; SD=0.05), using the alcohol screening instrument of the Uruguayan National Drug Board to assess adolescents' alcohol use (yes/no), a screening instrument for psychopathology and resilience (the adolescent self-report) and a socio-demographic questionnaire. Findings: Logistic regression analyses identified antisocial behaviour, substance use and negative emotionality ( F 2), disruptive and dysregulated behaviour ( F 8), higher age and recent death of a close relative as risk factors, while the number of close friends was identified as a protective factor for past year alcohol use (yes/no). No straightforward relationship was found between schools and the risk for the past year alcohol use. In addition, age, F 2, F 8 and recent death of a close relative appeared to be the most robust predictors. Research limitations/implications: The study was the first in Uruguay to relate adolescents' alcohol use to risk and protective factors. Given the cross-sectional nature of the study, causal relationships could not be determined. Originality/value: The study provides preliminary recommendations for policy makers and other stakeholders involved in youth affairs on core elements to focus on school-, community- and family-based alcohol prevention programmes for adolescents.